Optimization Pine Plantation Forest Management in Kediri FMU Regional Division II East Java - Andrie Ridzki Prasetyo; Muhamad Buce Saleh; Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2017)
Pine forest management today has not already reached its optimal state. The abnormal pine stand structure will cause a decrease in the production of pine resin. This study aimed to determine the optimal rotation of pine plantation forest and formulated the harvest scheduling to ensured optimal resin production. The determination of optimal rotation was conducted by modifying the Faustman formula to be applied on the condition in forest management in Perhutani. Simulation optimization of harvest scheduling was conducted by linear programming. Optimal rotation of pine forest plantation consists of timber rotation and resin rotation. The highest net present value of timber was obtained at 25 year cycles and the highest net present value of the resin was obtained at 35 year cycles. The inclusion of resin beneﬁt was resulting in lengthening the optimal rotation age. The abnormal stand structure was causing the fluctuations of pine resin production. Thus, the efforts to improve it was by applying the harvest scheduling framework. This study concluded that harvest scheduling which conducted over eight periods has made the abnormal stand structure into the normal forest condition. The existence of normal forest condition led to the certainty of pine resin production sustainability.